Complete mitochondrial genomes of the yellow-bellied slider turtle Trachemys scripta scripta and anoxia tolerant red-eared slider Trachemys scripta elegans. (3rd May 2016) - Yu, Danna; Fang, Xindong; Storey, Kenneth B; Zhang, Yongpu; Zhang, Jiayong
Abstract: The complete mitochondrial genomes of the yellow-bellied slider ( Trachemys scripta scripta ) and anoxia tolerant red-eared slider ( Trachemys scripta elegans ) turtles were sequenced to analyze gene arrangement. The complete mt genomes of T. s. scripta and elegans were circular molecules of 16, 791 bp and 16, 810 bp in length, respectively, and included an A + 1 frameshift insertion in ND3 and ND4L genes. The AT content of the overall base composition of scripta and elegans was 61.2%. Nucleotide sequence divergence of the mt-genome (p distance) between scripta and elegans was 0.4%. A detailed comparison between the mitochondrial genomes of the two subspecies is shown.